Edukasi Pencegahan Cacingan di SDN 019 Sungai Kunjang, Samarinda, Kalimantan Timur - Kurniawan, Hery; Alifa, Kika; Nabila, Hikma Hairatin; Pertiwi, Annisa Nurul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Soil-transmitted helminth infections remain a health problem among elementary school children in Indonesia because they lead to poor nutrition, reduced concentration in class, and lower productivity in the future. Prevention can be achieved through education on clean and healthy living habits, such as washing hands, keeping nails clean, wearing footwear, and regularly taking deworming medication as recommended. The community service activity carried out at SDN 019 Sungai Kunjang, Samarinda, East Kalimantan, aimed to increase students' knowledge about worm prevention. The implementation methods included recording student attendance, pre-tests, showing educational videos on worm infections, distributing leaflets, teaching students how to wash their hands with soap, and post-tests to measure student understanding. The results of the activity showed an increase in students' knowledge about worm prevention, as indicated by an increase in pre-test scores from 56.45 to 83.54 on the post-test.